Pengujian daya gabung galur S4 pada tanaman jagung (Zea mays L.)=Combining Ability of Maize S4 Lines (Zea Mays L.) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT This investigation was aimed to find out combining ability of maize inbred lines and their single cross hybrids. Ten parents and their 45 hybrids without reciprocals were evaluated in the dry seacon of 1987 at Jambegede Experiinent Farm Malang. According to the result of combining ability analysis it was found that the Muneng Sintetik-45-3-1-#, Muneng Sintetik-45-4-1-#, Muneng Sintetik-82-3-1-#, and Pool 2.145-1-1-# had the good gca_ Hybrids which have the good sca and gave the highest grain yield per plant are hybrids (Pool 2-145-1-1-# x Muneng Sintetik45-4.1-#) averaged 130,77 g, (Mojosari Erect-92-1-1-# x Pool 2-92-7-1-#) averaged 115,29 g, (Muneng Sintetik-82-2-1-# x Pool 2-145-1-1-#) averaged 115,24 g and (Pool 2-92-7-1-# x Muneng Sintetik-45-3-1- #) averaged 108,61 g. The grain yield of this four hybrids are 38,09 %, 21,74 %, 21,69 % and 14,69 % respectively more than Adana variety.